Hubungan Penggunaan Sistem Rujukan Terintegrasi (SISRUTE) Dengan Tingkat Keberhasilan Kecepatan Penanganan Gawat Darurat Kasus Stroke Di Ambulan Gawat Darurat (AGD) Dinas Kesehatan DKI Jakarta - Fitri Wahyuningsih; Bambang Suryadi; Agus Purnama (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The success of stroke treatment is determined by the speed and accuracy of treatment. The golden time in treating stroke is ± 3 hours. Integrated Referral System SISRUTE is a tool that facilitates the transfer of health services between various health facilities.Rapid reporting through the web application is facilitated by this system.. The aim of this research is the relationship between the use of an integrated referral system (SISRUTE) and the speed of success in emergency treatment of stroke cases in the0AGD0of the0DKI0Jakarta0Health Office. The research method that will be used is an analytical research design with a correlational The design was cross-sectional, with a population of 340 participants and 77 participants chosen for the sample size. Using the parametric Chi-Square test. The results show a relationship between using the integrated road system (SISRUTE)..and the success rate of speed of emergency treatment of stroke cases in the0AGD0of the0DKI0Jakarta Health0Office0with a p-vlue of 0.014 < 0.05. Conclusion: The use of an integrated referral system can influence the success rate of stroke emergency treatment.